Interactions with membrane lipids and SNARE complex underlie dual roles for calcium-dependent activator protein for secretion (CAPS) in large dense-core vesicles (LDCVS) priming - Stevens, David R. (2015)
CAPS (Calcium-dependent activator protein for secretion), was discovered as a soluble factor required for catecholamine secretion from PC12 cells. CAPS facilitates release of dense-core vesicles and release of neurotransmitters. In vertebrates CAPS is required for priming of synaptic vesicles and dense-core vesicles in neurons and in catecholamine release from the adrenal medulla. The pleckstrin homology domain of CAPS has been shown to mediate an interaction with the plasma membrane. An interaction with SNARE proteins and assembled SNARE complexes requires the Munc13 homology domain. The interaction with SNARE components facilitates SNARE complex formation, the molecular basis of the priming reaction, while interactions with the phosphoinositol 4,5 bisphosphate (PI(4,5)P2) rich areas of the plasma membrane localize CAPS at the release site but may also promote the fusion of primed vesicles. CAPS splice variants lacking the Munc13 homology domain but with an intact pleckstrin homology domain promote priming to the readily releasable pool while CAPS splice variants with a deletion in the pleckstrin homology domain promote catecholamine release, albeit at slower rates. These results confirm a dual action of CAPS dependent on the Munc13 homology- and the pleckstrin homology domains, respectively.